Brewer’s spent yeast polysaccharides: feasibility of extracts for the development of biomaterials - Viduêdo, Sérgio Augusto Morais (2022)
Brewer’s spent yeast is the second largest by-product of the brewing industry, being an abundant, recyclable and cheap material that is frequently discarded. This material is composed of several compounds of added value and with proven biological activity, namely its polysaccharides, with emphasis on glucans and mannoproteins. These polysaccharides can be solubilized from brewer’s spent yeast by mild or more drastic extraction methods, leading to the obtention of different extracts with distinct compositions. Several extracts were tested in the production of films, successfully: a hot water extract (57 % protein, 34 % total carbohydrates, 23 mol% glucose, 59 mol% mannose) and two alkaline extracts, one of 0.1M KOH (29 % protein, 26 % total carbohydrates, 46 mol% ribose, 19 mol% glucose, 37 mol% mannose) and other of 4M KOH (23 % protein, 74 % total carbohydrates, 22 mol% ribose, 30 mol% glucose, 48 mol% mannose). Production of films was performed using the solvent casting method with the use of glycerol as a plasticizer, genipin as a cross-linker and sepiolite as a filler. For each extract, different parameters were adjusted for the successful production of films: 20 mg/cm2, 25 % (w/w) glycerol, 0.05 % (w/v) genipin, 25 ºC, 24 hours (hot water extract); 20 mg/cm2, 50 % (w/w) glycerol, 25 ºC, 24 hours (0.1M KOH extract); 20 mg/cm2, 50 % (w/w) glycerol, 0.2 % (w/v) genipin, 3.5 % (w/v) sepiolite, 35 ºC, 16 hours (4M KOH extract). Characterization of films was done using mechanical, wettability, solubility and water vapour permeability tests. The films exhibited different mechanical characteristics (Young’s Modulus 53-337 MPa, tensile strength 1-8 MPa, elongation 3-24 %) but they were all of a hydrophilic nature (water contact angles 30-90 º), being soluble in water (solubility values of 51 to 93 %) and with low permeability to water vapour (water vapour permeability value of 2.83 × 10-16 g Pa-1 h-1 m-1). Films produced revealed that different brewer’s spent yeast extracts, can be used to produce different biomaterials, in the absence or presence of cross-linker agents or fillers, which may turn into food and biomedical applications.